The Inter-State Complaint under the African Charter on Human and People’s Rights: a Lesson from the European Regional System - J. Adams, Adoga-Ikong; Jacob Udo, Edidiong; Pascal Bekonfe, Aboh (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
Like every other regional system, the African Charter on Human and People’s Rights have set up an inter-state complaint procedure where individual(s) states or even organizations can report any violation of human rights meted on him or it as the case may be. In doing this, a body is put in place to implement the provisions of the charter on human rights. This body which is known as the African Commission is responsible for the compliant member of states, individuals and even organizations. How much has the commission performed in the implementation of these rights? Are they some lacunae that needed to fill? What is the way forwards? There are indeed lacunae in the implementation of the rights under the African Charter among which are: one, the inability of the individual claiming violation of his rights to present a complaint against his own or another state, two the fact that the Charter does not set a time limit at which the aggrieved party can approach the commission for redress. Under the European Regional System, the above problems have been taken care of by the convention. Here the provision of Article 25 of the Convention allows an individual to present a complaint against his state or even another state for investigation. This is one of the laudable achievements of the European Regional System. This work, therefore, sought a suggestion for the emulation of the European Regional System.